2015
DOI: 10.1097/meg.0000000000000387
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for band-induced ulcer bleeding after prophylactic and therapeutic endoscopic variceal band ligation

Abstract: Our EVBL-induced ulcer bleeding rate was low, but associated with significant mortality. Highest rates were observed following EVBL for acute variceal haemorrhage, for which EVBL is unavoidable. The incidence was lower following prophylactic EVBL, with the MELD score being the predominant risk factor. Reflux oesophagitis requires further investigation as a potentially modifiable risk factor for EVBL-induced ulcer bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
61
2
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 19 publications
11
61
2
1
Order By: Relevance
“…This mortality rate was similar to a previous report of 28% by Sinclair et al, [22] but lower than another report of 52% by Vanbiervliet et al [12] In the study by Sinclair et al, the use of prophylactic antibiotics was not recorded. However, in the study by Vanbiervliet et al, the cause of death in the majority of the patients was sepsis, and this was explained by the low rate of prophylactic antibiotic usage (62%).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This mortality rate was similar to a previous report of 28% by Sinclair et al, [22] but lower than another report of 52% by Vanbiervliet et al [12] In the study by Sinclair et al, the use of prophylactic antibiotics was not recorded. However, in the study by Vanbiervliet et al, the cause of death in the majority of the patients was sepsis, and this was explained by the low rate of prophylactic antibiotic usage (62%).…”
Section: Discussionsupporting
confidence: 90%
“…The incidence of EVL-induced ulcer bleeding in our study is higher than recently published rates of about 2.8%. [12,22] However, the rate of severe bleeding, which was defined as bleeding associated with hypotension or death, was 2.6%, similar to the previous reports. The high proportion (23%) of follow-up endoscopies within 1 to 2 weeks after EVL made it possible to detect minor EVL-induced ulcer bleeding and may explain the high prevalence in our study.…”
Section: Discussionsupporting
confidence: 87%
“…[17,18] In elective procedures, higher MELD score and reflux esophagitis were associated with significant EVLinduced ulcer hemorrhage. [23] The number of rubber bands applied per patient seems to have no correlation with rebleeding in most trials. [8] A prospective study showed that the placement of more than six bands per session was not associated with better outcomes but rather with prolonged banding, increased procedure time and more misfired bands.…”
Section: Risk Factorsmentioning
confidence: 99%
“…In patients (n = 609) with EVL for bleed prophylaxis, the post-EVL ulcer bleed rate was 1.5% with 22% mortality, higher MELD, and reflux esophagitis were predictors of bleed. 1 The bleeding from post-EVL ulcers can be managed by pharmacotherapy; endoscopic banding or sclerotherapy, and transjugular intrahepatic portosystemic shunt (TIPSS). 2 The index patient has failed endoscopic approach and pharmacotherapy.…”
mentioning
confidence: 99%